The Contribution of Islamic Financial Institutions to the Empowerment of MSMEs in the Framework of Sustainable Development Goals - Ahmad Haekal; Zal Sabila; Besse Astirah Ramda (Universitas Islam Negeri Raden Intan, 2025)
Islamic financial institutions have an important role in empowering micro, small, and medium enterprises (MSMEs) to support sustainable development. In Palu City, Central Sulawesi, MSME empowerment programs have been implemented, yet their alignment with the Sustainable Development Goals (SDGs) remains limited. This study analyzes the role of Islamic financial instruments in integrating the SDGs framework into MSME empowerment. Using a qualitative approach, data were collected through interviews, observation, and documentation involving Bank Syariah Indonesia (BSI) KCP Palu Plaza and MSME actors and analyzed thematically. The results indicate that the People’s Business Credit (KUR) program effectively enhances MSME access to Sharia-compliant financing and contributes to SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure). However, non-financial support, such as mentoring and training, has not been optimally implemented. This study highlights the need to strengthen integrated Islamic financing and community-based capacity building to achieve sustainable MSME empowerment. Keywords: Islamic Finance, MSME Empowerment, Sustainable Development Goals (SDGs), Sharia Financing, Community Based Mentoring